Re‐treatment with radium‐223: 2‐year follow‐up from an international, open‐label, phase 1/2 study in patients with castration‐resistant prostate cancer and bone metastases. Issue 14 (23rd August 2019) - Sartor, Oliver; Heinrich, Daniel; Mariados, Neil; Méndez Vidal, Maria José; Keizman, Daniel; Thellenberg Karlsson, Camilla; Peer, Avivit; Procopio, Giuseppe; Frank, Stephen J.; Pulkkanen, Kalevi; Rosenbaum, Eli; Severi, Stefano; et al.
Abstract: Background: Radium‐223 dichloride (radium‐223) is approved for patients with castration‐resistant prostate cancer (CRPC), symptomatic bone metastases, and no visceral disease using a dosing regimen of 6 injections (55 kBq/kg intravenously; 1 injection every 4 weeks). Early results from international, open‐label, phase 1/2 study NCT01934790 showed that re‐treatment with radium‐223 was well tolerated with favorable effects on disease progression. Here we report safety and efficacy findings from 2‐year follow‐up of the radium‐223 re‐treatment study. Methods: Patients with CRPC and bone metastases who completed 6 initial radium‐223 injections with no disease progression in bone and later progressed were eligible for radium‐223 re‐treatment (up to 6 additional radium‐223 injections), provided that hematologic parameters were adequate and chemotherapy had not been administered after the initial course of radium‐223. Concomitant cytotoxic agents were not allowed during re‐treatment but were allowed at the investigator's discretion during follow‐up; other concomitant agents for prostate cancer (including abiraterone acetate or enzalutamide) were allowed at investigator's discretion. The primary objective was safety. Exploratory objectives included time to radiographic bone progression, radiographic progression‐free survival (rPFS), time to total alkaline phosphatase (tALP), and prostate‐specific antigen (PSA) progression, overall survival (OS), time to first symptomatic skeletal event (SSE), and SSE‐free survival, all calculated from re‐treatment start. Evaluation of safety and exploratory efficacy objectives included active 2‐year follow‐up. Safety results from active follow‐up and updated efficacy are reported. Results: Overall, 44 patients were re‐treated with radium‐223; 29 (66%) completed all 6 injections, and 34 (77%) entered 2‐year active follow‐up, during which no new safety concerns and no serious drug‐related adverse events were noted. rPFS events (progression or death) occurred in 19 (43%) of 44 patients; median rPFS was 9.9 months. Radiographic bone progression occurred in 5 (11%) of 44 patients. Median OS was 24.4 months. Median times to first SSE and SSE‐free survival were 16.7 and 12.8 months, respectively. Median time to tALP progression was not reached; median time to PSA progression was 2.2 months. Conclusions: Re‐treatment with radium‐223 in this selected patient population was well tolerated, led to minimal hematologic toxicity, and provided continued disease control in bone at 2‐year follow‐up.